(untitled) - Miesfeld, Roger L. (New York, 1999)
The book is divided into several sections and moves from basic to advanced topics while providing a concise overview of fundamental concepts in modern biotechnology. Each chapter concludes with a Laboratory Practicum describing a hypothetical research objective and the sequence of steps that are most often used to investigate biological questions using molecular genetic methods
Keywords: Sinh học phân tử,Nucleic acids.,Molecular biology.,Sinh học phân tử